2018
DOI: 10.1136/bmjopen-2018-023917
|View full text |Cite
|
Sign up to set email alerts
|

‘Secretly, it’s a competition’: a qualitative study investigating what helped employees quit smoking during a workplace smoking cessation group training programme with incentives

Abstract: ObjectivesSmoking cessation programmes in combination with financial incentives have shown to increase quit rates in smokers, but it is not clear which elements of this intervention help smokers to succeed in their quit attempt. The aim of this study was to explore the view of successful and unsuccessful quitters about which factors had affected their ability to quit smoking.DesignSemistructured qualitative interviews were conducted and analysed using the Framework method.SettingInterviews were conducted in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This is consistent with previous research which found that, even in contexts in which smokers quit smoking at higher rates in an incentives group versus a control group, successful participants attributed their success to intrinsic motivation and not the incentives. 30 31 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous research which found that, even in contexts in which smokers quit smoking at higher rates in an incentives group versus a control group, successful participants attributed their success to intrinsic motivation and not the incentives. 30 31 …”
Section: Discussionmentioning
confidence: 99%